Antibiotic Resistance in Salmonella sp. Isolated from Layer Chicken in North Lombok, West Nusa Tenggara - Agustin, Alfiana Laili Dwi (Universitas Pendidikan Mandalika, 2025)
Resistance antibiotic Salmobnella sp. difficult to recover when treated. Antibiotic resistance can occur due to inappropriate use of antibiotics, such as incorrect dosage, incorrect indications, and incorrect use. This research was conducted based on reports from farmers that their chickens did not recover after being given antibiotics when they had diarrhea. The results of interviews with farmers show that they usually use antibiotics without advice from a veterinarian, they can buy antibiotics freely at poultry shops. The samples in this study were taken from egg-laying chicken farms in Santong village, North Lombok, West Nusa Tenggara. Samples were taken from farms with the most reported cases of persistent diarrhea, with 32 samples taken from two farms 16 samples each. Samples were taken using sterile cotton buds from chickens showing symptoms of chalky diarrhea, the results of the rectal swab from each chicken were inserted into the brain heart infusion (BHI) transport media and placed in an ice box to then be planted in the media in the laboratory. From BHI media, cotton buds were swabbed on XLD media, the colonies that grew were purified and then tested for gram and biochemistry. esult was determined by standard biochemical procedures using Bergeyʼs Manual. Identified salmonella bacteria were tested with the antibiotics trimethoprim, ampicillin, ciprofloxacin, penicillin G, and erythromycin. Isolation results from 32 samples tested, 22 samples showed Salmonella sp. isolates. The results of the antibiotic resistance test showed that 22 isolates were resistant to penicillin G, ciprofloxacin was no longer able to kill 21 isolates resistant, and 11 isolates were resistant to the antibiotics erythromycin and ampicillin. The evidence of antibiotic resistance in Salmonella sp. bacteria from layer chickens in North Lombok can have an impact on human health, one health and can be spread through livestock food.